Metallographer's guide : practice and procedures for irons and steels - Bramfitt, B. L. (ASM International, 2001)
Concentrating on optical metallography, this guide presents information on the microstructures that will be encountered, how these microstructures were created, and how they can be altered by heat treatment and other means. Because Bramfitt (Homer Research Laboratories, Bethlehem Steel Corporation) and Benscoter (materials science and engineering, Lehigh U.) feel very strongly that without proper knowledge of the metallurgy of the material being prepared the metallographist can't interpret microstructures developed, basic understanding of steel microstructures is emphasized. Other material includes the operation of metallurgic microscopes, typical tools in a metallurgic laboratory, and specimen preparation procedures. Also included is a brief history of early metallographers. Annotation c. Book News, Inc., Portland, OR (booknews.com).